Is there a penalty for going to trial in Spain? Plea bargaining and courtroom efficiency - Kemp, Steven (European journal of criminology, 2024)
The plea bargain is now the most frequent mode of conviction in many countries, yet several problems have been highlighted, such as loss of rights, enhanced sentencing disparities or increased false confessions. A central element to many of the issues is the sentence discount obtained by pleading or the penalty associated with going to trial. However, outside the United States and the United Kingdom, there have been few attempts to analyse plea-trial disparities, and in Spain research is almost non-existent. To help fill this gap, the present article provides the first quantitative examination of plea discounts and trial penalties in Spain. Regression models, covariate balancing propensity score and counterfactuals are estimated to show that, in comparison to going to trial, agreeing to a plea in the initial stage of the process is associated with shorter sentences and, more importantly, the results demonstrate that the probability of entering prison is significantly greater for those convicted at trial compared to both plea types analysed. In addition, evidence of concerning inequalities is found between Spanish nationals and foreigners. The findings indicate courtroom actors may be working conjointly to expedite the criminal process and we discuss the implications of this in relation to the fundamental principles of criminal justice systems, such as proportionality, equality and the presumption of innocence.